PENGARUH TOTAL QUALITY MANAGEMENT (TQM) TERHADAP KINERJA MANAJERIAL - Mashoeda, Ivena; Waluyowati, Nur Prima (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Companies in facing global competition are expected to have competitive advantages that can be used by consumers to choose a company. The objective of this research is to identify the partial and simultaneous effect of Customer Focus, Continuous Improvement, Employee Empowerment and Management Commitment on the managerial performance of PT. Adhi Karya (Persero) Tbk. in the construction project of the Regional Office Building of BRI in Malang. This research is categorized into explanatory research, which aims to identify the effect of the independent variable, i.e., Customer Focus, Continuous Improvement, Employee Empowerment and Management Commitment on the dependent variable, i.e. managerial performance (Y) using quantitative approach. Here a sample of 59 respondents was used. The results of the multiple linear regression have led to a finding that Total Quality Management has a negative and insignificant effect on managerial performance. Therefore, this research suggests PT. Adhi Karya (Persero) Tbk. to improve the implementation of Total Quality Management (TQM) so that the company can get a better managerial performance in their projects.